DRUG SALES SYSTEMON PT. INDOFARMA - Andri Hermawan; Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2000)
PT. Indofarma is a pharmaceutical company engaged in the production, maintenance and distribution of drugs at the same time to all levels of society. One factor that makes the establishment of pharmaceutical companies is the implementation of the national health development through distribution of drugs, safety and quality in sufficient quantity and affordable for the public. In the development of PT. Indofarma has in the management branch distribution (marketing) to serve the marketing to the community, so that PT. Indofarma orders in large quantities and the resultservices in the marketing process is less rapid in accordance with the specified time.Computerization in terms of data integration in the pharmaceutical marketing activities companyis indispensable for the accuracy of these data, it clearly requires a good system, too. Through the writing of this study tried to overcome the problems in the System Drug Sales at PT. Indofarma so that they can implement better systems.